A bio-inspired technique for servicing networked robots. (4th January 2012) - Godfrey, W. Wilfred; Nair, Shivashankar B.
Bio-inspirations have paved a way for finding new and novel ways of optimisation in several application scenarios. Virtual pheromones have been used widely for routing in mobile ad-hoc networks and wireless sensor networks as also for communication among robots. In this paper, we describe a multi-robot system wherein mobile agents act as code carriers and in turn facilitate execution of tasks by the robots. Networked robots that need a code to execute an allotted task diffuse, onto their neighbours, pheromones that specifically attract those mobile agents that carry the required code as their payload. The agents move around the network in a conscientious manner but on sensing a pheromone, home onto the concerned robot and provide the code. We compare this pheromone-conscientious method with other mobile agent-based patrolling and resource discovery strategies and portray the relevant results and conclude that the pheromone-conscientious strategy is more conservative in terms of both time and energy consumed.